Упростить выражение и решить 3(2m-4)-2(2m-7) m = -3 3/7-2(2x-3)-4x+(5*8x) если x=-2.17

0 голосов
38 просмотров

Упростить выражение и решить
3(2m-4)-2(2m-7) m = -3 3/7
-2(2x-3)-4x+(5*8x) если x=-2.17


Алгебра (451 баллов) | 38 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

1) 6м-12-4м+14= 2м+2
при м= -3 следует 2*(-3)+2=-6+2=-4
при м= 3/7 следует 2*3/7+2=6/7+2=2целых6/7

2)-4х+6-4х+40х=48х+6
при х= -2 следует 48* (-2)+6=-96+6=-90
при х= 17 следует 48*17+6=816+6=822

(1.4k баллов)
0 голосов

Если m = -3 3/7   то,
3(2m-4)-2(2m-7)=3*2m-4-2*2m+7=1*4m+3=1*(-3 3/7)+3= -6 3/7

(203 баллов)